Desain Metode Proteksi Katodik Dengan Arus Paksa ( Impressed Current ) Pada Pipa Dermaga - Sufrianti, Jusni; Hamzah, Amir (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Impressed Current Cathodic Protection (ICCP) is protection by giving electrons to the pipe material using a source of electric current from outside the system. In this article the design of cathodic protection using the impressed current method on the pier pipe contained in PERTAMINA Dumai's RU 2 is to protect 12 m long pipes in the water with a total protection current of 528 A, the result of analysis producing a rectifier specification for the design, = 19,95 V goes to Junction Box 1( pier pipes connected to junction box 1) and = 18,07 towards Junction Box 2 ( pier pipes connected to junction box 2 ), = 22,17 V on transformer 1 ( electrical supply for junction box 1 ), and = 20,08 Von transformer 2 ( electrical supply for junction box 2 ), = 475,12 A and Rectifer Power Capacity = 104,528 kVA, and the anode needed 67 Mixel Metal Anode (MMO). Keywords: PLTSa, Incenerator, Feasibility Analysis, Technical Economics